Kualitas Layanan Inaportnet pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas I - Eka Sukmawati; Dian Lieska Ocviany; Indarno Sugeng Rahardjo; Mahardhika Andiansyah; Marthaleina Ruminda; Yosi Pahala; Sugiyanto Sugiyanto; Devi Ratnasari (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This research aims at determining the quality of Inaportnet services by comparing service performance and service user expectations. A quantitative approach with the Importance Performance Analysis (IPA) method was used with a saturated sample of 23 respondents. Primary data was collected by distributing questionnaires. The analysis was carried out to determine the suitability of service performance to the expectations of service users which is described through the IPA Matrix in the form of a Cartesian diagram. The results showed that the total level of conformity was 94.46% so the suitability of the overall service performance was still below the expectations of service users. However, judging by the Interpretation Guidelines, the level of suitability of service users was very satisfied. Gap analysis was used to find out whether there was a gap in service at the Port in Banten by looking for the difference in the value of performance and the value of importance (expectations). The results of the Gap Analysis calculation (gap score) showed that each item of the instrument was negative, which means that it still needs to be reviewed and improved on each item of the instruments